Job Insecurity and Impression Management: Which Is the Horse and Which Is the Cart When It Comes to Job Performance? - Lopez-Bohle, S (Emerald Group Holdings Ltd., 2020)
Purpose: The purpose of this paper is to test competing models of the relationship between job insecurity and two forms of impression management (self- and supervisor-focused) on job performance. Specifically, does job insecurity lead to greater subsequent impression management; or, does preventative use of impression management subsequently lead to reductions in job insecurity? Additionally, how do these both relate to in-role performance? Design/methodology/approach: Using two-wave survey data collected from 184 working adults in the USA and the two-step approach recommended by Cole and Maxwell (2003) and Taris and Kompier (2006), the authors tested cross-lagged relationship between job insecurity and both forms of impression management by comparing four different models: a stability model, a normal causation model (with cross-lagged paths from T1 job insecurity to T2 impression management), a reversed causation model (with cross-lagged paths from T1 impression management to T2 job insecurity) and a reciprocal causation model (with all cross-lagged paths described in the normal and reversed causation model). Findings: Results were supportive of the reversed causation model which indicated that greater use of supervisor-focused impression management at Time 1 predicted lower levels of job insecurity at Time 2 (after controlling for prior levels of job insecurity); moreover, job insecurity at Time 1 was then significantly associated with more positive in-role behaviors at Time 2. Moreover, the test of the indirect effect between T1 impression management and T2 performance was significant. Originality/value: These results suggest that impression management clearly plays an important role in understanding the relationship between job insecurity and job performance. However, employees appear to utilize impression management as a means of pre-emptively enhancing their job security, rather than as a tool to reactively cope with perceived job insecurity. © 2019, Emerald Publishing Limited.